Pattern of Suicide Attempts in Southern Nepal: A Multi-Centered Retrospective Study - Thapaliya, Suresh; Gupta, Anoop Krishna; Tiwari, Suraj; Belbase, Mohan; Paudyal, Shreya (Med Phoenix, 2018)
Background: Suicide has become a major public health issue in low income underdeveloped countries like Nepal. In Nepal, suicide research based on General Hospital Psychiatry Unit (GHPU) settings can be informative to explore the trend in suicidal behaviors. In this study, we aimed to study the pattern of suicide attempts in Southern Nepal by including retrospective suicide attempt cases registered in the three GHPU centers. Methods: The study included 116 survivors of suicide attempts registered over a period of six months (Jan, 2017 to July, 2017) at three centers in Southern region of Nepal. The cases were referred from medical emergency or other medical departments for psychiatric evaluation. They underwent evaluation by at least one consultant psychiatrist and received appropriate interventions. Results: Majority of the victims were female (68%), belonging to younger age group (90%) with one third in adolescent age group and homemakers (32%) or students (31%) by occupation. The most common method of attempt was self poisoning with pesticides (78.4%) followed by medication overdose (8.6%) and hanging (7.8%). Most of the attempts (82.7%) were impulsive in nature. Mental illness was diagnosed in 60 % of the cases, mainly depressive disorder, and adjustment disorder. Most of the attempts (87%) were triggered by psycho-social factors before the attempt, mainly interpersonal conflicts. Conclusions: The pattern shows predominance of female gender, younger age group, a role of mental illness, impulsivity and psychosocial factors in suicide attempts. Future research should focus on these aspects to develop effective prevention strategies. Med Phoenix. Vol. 3, Issue. 1, 2018, Page: 41-47